2016
DOI: 10.1063/1.4958593
|View full text |Cite
|
Sign up to set email alerts
|

Composite of [HA/PMMA] for 3D-printer material application

Abstract: Abstract. Synthetic hydroxyapatite (HA) and polymethylmethacrylate (PMMA) are among biomaterials that individually has been used in bone defect restoration. Pure HA powder is bioactive and biocompatible material, but it was difficult to be shaped into certain geometry as needed in many cases of restoration. While, PMMA may cause necrosis at the bonecement interface due to the heat released during polymerization. In shaping technology, a 3D Printer technology is capable to cope a complex geometry and shape, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 16 publications
0
6
0
1
Order By: Relevance
“…However, there are several disadvantages for PMMA, such as brittleness and release of heat during polymerization, which can lead to necrosis at the bone cement interface. Thus, PMMA needs to be further modified to improve its formation and ameliorate stress shielding [195]. In another study by Tontowi et al [195], PMMA powder was blended with methyl methacrylate (MMA) liquid to obtain PMMA pasta first, such that the PMMA pasta composited with HA nanopowder could be used for 3D printing.…”
Section: Hydroxyapatite (Ha)/polymethyl Methacrylate Nanocompositesmentioning
confidence: 99%
“…However, there are several disadvantages for PMMA, such as brittleness and release of heat during polymerization, which can lead to necrosis at the bone cement interface. Thus, PMMA needs to be further modified to improve its formation and ameliorate stress shielding [195]. In another study by Tontowi et al [195], PMMA powder was blended with methyl methacrylate (MMA) liquid to obtain PMMA pasta first, such that the PMMA pasta composited with HA nanopowder could be used for 3D printing.…”
Section: Hydroxyapatite (Ha)/polymethyl Methacrylate Nanocompositesmentioning
confidence: 99%
“…Assuming that TSS would increase with turbidity intensities as stated by [11], the relation between TSS and turbidity was evaluated. TSS concentration is proportional to the increase of turbidity and inversely proportional to the water brightness.…”
Section: Tss Versus Turbiditymentioning
confidence: 99%
“…As a base in dental materials, there are a number of studies related to PMMA composites and polymer blends as printing materials, such as PMMA/hydroxyapatite-zirconia, PMMA-based denture, PMMA/hydroxyapatite, PMMA/TiO2 based denture, PMMA/silica filaments. [1,2,[14][15][16][17] Alshaikh et al [1] prepared 3Dprinting denture base (acrylic resin) without and with the addition of 1-5 wt.% of silane-modified ZrO2 nanoparticles, the specimens were printed in a rectangular shape via UV curing 3D-printing method and then using the same polishing procedure. Their study revealed that heat-polymerized acrylic resin showed higher mechanical properties when compared with those of the unmodified 3D-printed resins, however, the addition of ZrO2 nanoparticles improved the mechanical properties of 3D-printed resins.…”
Section: Introductionmentioning
confidence: 99%
“…As a base in dental materials, there are a number of studies related to PMMA composites and polymer blends as printing materials, such as PMMA/hydroxyapatite‐zirconia, PMMA‐based denture, PMMA/hydroxyapatite, PMMA/TiO 2 based denture, PMMA/silica filaments. [ 1,2,14‐17 ] Alshaikh et al . [ 1 ] prepared 3D‐printing denture base (acrylic resin) without and with the addition of 1‐5 wt.% of silane‐modified ZrO 2 nanoparticles, the specimens were printed in a rectangular shape via UV curing 3D‐printing method and then using the same polishing procedure.…”
Section: Introductionmentioning
confidence: 99%